Sinergi Pengabdian Masyarakat dalam Penguatan Ekonomi dan Pelestarian Budaya Lokal di Desa Cikeusal, Tasikmalaya - Nurul Frasiska; Iksan Fauzan Andriana; Silviani Silviani; Shelvira Noerachmi (Journal of Empowerment Community, 2026)
Community service activities through the Real Work Lecture (KKN) program in Cikeusal Village, Tanjungjaya District, Tasikmalaya Regency, were carried out to strengthen the local economy and preserve traditional culture as a social identity of the community. A participatory approach was used through observation, interviews, training, and collaboration between students, village officials, MSMEs, and arts groups. The empowerment program focused on strengthening MSMEs based on local products such as palm sugar and noga through digital marketing training, packaging innovation, and simple financial literacy. Meanwhile, the cultural aspect was directed at documenting and revitalizing the traditional art of Terebang Gébés which has high religious and social values. The results of the activities showed an increase in knowledge of MSMEs in business promotion and management, as well as increased participation of the younger generation in traditional arts activities. This cross- sector collaboration demonstrates that the synergy of community service can encourage the strengthening of the creative economy while maintaining the sustainability of local cultural heritage as part of sustainable village development.